Prototype for soil mechanical resistance measurement with chisel plow automated control - Machado, Thiago M.; Lanças, Kléber P. [UNESP] (FapUNIFESP (SciELO), 2016)
In Brazil, there are several available models and systems to measure soil compaction; however, the data generated by such equipment have to be processed and interpreted, making the process expensive. Our study aimed to evaluate a prototype of instrumented rods to identify soil compacted layers and control chiseling depth, and compared it to a conventional system at a fixed depth of 0.35 m. In order to compare them, we assessed the following parameters: hourly fuel consumption, operational fuel consumption, drawbar power, average power, average speed, slipping, tractor effective field capacity and response time. Our results showed that mechanical chiseling at variable depths reduced in 26% the operational fuel consumption and increased in 14% the effective field capacity. Furthermore, the prototype of chisel plow automated control generated maps displaying spatial variability of soil mechanical resistance with resolution, sampling density and high operating capacity.
Keywords: Chiseling; Precision agriculture; Soil compaction